Kontribusi Green Investment dan Good Corporate Governance Terhadap Pengungkapan Emisi Karbon - Gunawan, Maulina Septa Ning; Erry Andhaniwati (Al-Buhuts, 2024)
The purpose of this research to determine the relationship between green investment and good corporate governance to carbon emissions disclosure. GCG as proxied by independent commissioners, audit committee, board of directors, managerial ownership, and institutional ownership. The study encompasses 82 raw products sector companies that are listed on the Indonesia Stock Exchange (BEI) between 2019 and 2022. The purposive sampling approach was used to pick 60 samples for the sample. WarpPLS 8.0 software was used to test the partial least square (PLS) study investigation. The findings of the study demonstrate that green investments has no contribute on the disclosure of carbon emissions. In the interim, GCG helps with the disclosure of carbon emissions.Based on these findings, companies are expected to continue to increase the transparency of information regarding environmental disclosures, especially regarding carbon emission disclosures.